Van der Waals integration of high-κ perovskite oxides and two-dimensional semiconductors - Yang, Allen Jian (2022)
Two-dimensional semiconductors can be used to build next-generation electronic devices with ultrascaled channel lengths. However, semiconductors need to be integrated with high-quality dielectrics—which are challenging to deposit. Here we show that single-crystal strontium titanate—a high-κ perovskite oxide—can be integrated with two-dimensional semiconductors using van der Waals forces. Strontium titanate thin films are grown on a sacrificial layer, lifted off and then transferred onto molybdenum disulfide and tungsten diselenide to make n-type and p-type transistors, respectively. The molybdenum disulfide transistors exhibit an on/off current ratio of 108 at a supply voltage of 1 V and a minimum subthreshold swing of 66 mV dec−1. We also show that the devices can be used to create low-power complementary metal–oxide–semiconductor inverter circuits.